Riskiness-minimizing spot-futures hedge ratio - Chen, Yi-Ting; Ho, Keng-Yu; Tzeng, Larry Y. (Journal of Banking & Finance, 2014)
In this paper, we propose a new spot-futures hedging method that determines the optimal hedge ratio by minimizing the riskiness of hedged portfolio returns, where the riskiness is measured by the index of Aumann and Serrano (2008). Unlike the risk measurements widely used in the literature, the riskiness index employed in our method satisfies monotonicity with respect to stochastic dominance. We also provide an empirical example to demonstrate how to estimate and test this optimal hedge ratio in equity data by the method-of-moments.